Competencies of human resource management practitioners in the upland Municipalities of Ilocos Sur - Dangle, Arnold M. (San Fernando City, La Union : [s.n.], 2014)
This study aimed to find out the level competencies of the Human Resource Management Practitioner (HRMP) in the Upland Municipalities of Ilocos Sur. It specifically looked into the profile of the HRMP along educational attainment, number of years in HRM practice, and trainings/seminars attended; level of their competencies in terms of technical/professional, human/behavioral, organizational/core, and supervisory/managerial. From here, the capabilities and constraints as well as the problems were also probed into. Finally, a validation of the proposed strategic human resource management interventions to enhence the level of competencies of the HRMP in the Upland Municipalities of Ilocos Sur.
Bibliography: pages 134-139.
CHED-La Union
Keywords: Personnel management